(untitled) (Research, Society and Development, 2020)
This paper presents propositions and contexts about the Rural Education course at the Federal University of Amapá (UNIFAP)and its institution at the university campus in the municipality of Mazagão. With a qualitative approach we explore the implementation and pedagogical proposal of the Degree in Rural Education (LEDOC) as part of public education policies and as a human right and public training. For this, we performed a documentary and descriptive analysis of the Pedagogical Project of the Course (PPC). The analysis of the data considers that educational policy in the formation of rural subjects in the State of Amapá reveals that the course in the city of Mazagão is an achievement and a challenge for the Federal University of Amapá, since it breaks with the traditional model of undergraduate degrees, maintained by the institution, as well as a major advance in public education policies aimed at serving the rural peoples.